Statin Underprescribing for Primary Prevention of Cardiovascular Disease among Elderly Diabetic Patients in Saudi Arabia (Asian Journal of Pharmaceutics (AJP), 2025)
Objectives: This study aims to assess the rate of statin underprescribing among at-risk elderly diabetic patientsin Saudi Arabia, as a primary prevention for cardiovascular disease. Materials and Methods: A retrospectivecross-sectional data of elderly diabetic patients were obtained from the electronic database of the AcademicTertiary Center in Jeddah, Saudi Arabia. Data were retrieved from January to December 2020. Diabetic patientsaged 65–79 with an atherosclerotic cardiovascular disease score of 7.5% and above were included in the study.Descriptive statistics, Chi-square test, and multivariate logistic regression were used to analyze data. P < 0.05was considered statistically significant. Results: A total of 167 patient records were included in this study. Thecohort included patients with intermediate risk (n = 121, 62.5%) and high risk (n = 46, 27.5%) of developingatherosclerotic cardiovascular disease. The rate of statin underprescribing among the study group was 52.7%(n = 88). The predictors of statin use patterns among elderly patients with diabetes and cardiovascular risk wereobesity (P = 0.045) and smoking (P = 0.015). Conclusion: Over half of the study group, despite having riskfactors, were not taking statin therapy. Clinicians should consider initiating statin therapy for all patients at risk ofatherosclerotic cardiovascular disease while optimizing other medications to control blood pressure and glucose.